Physical Resource Management in Covid-19 Pandemic Era for Effectiveness of Secondary Schools in Rivers State. - Chimekwele, Kingsley; William-Yobo, Charity Barine (International Journal of Educational Management, 2021)
The study investigated physical resource management in covid-19 pandemic era for effectiveness of secondary schools in Rivers State.Descriptive survey design was adopted in the study; the population of study comprised of 261 principals and 7619teachers in the public secondary schools in Rivers State. The stratified and simple random sampling technique was used to draw a sample of 52 principals and 1524 teachers which represented 20% of the total population. The instrument for data collection was the questionnaire titled “Physical Resource Management in Covid-19 Pandemic Era for Effectiveness of Secondary Schools Questionnaire (PRMC-19PEESSQ)” which was validated by two experts in the Department of Measurement and Evaluation, Faculty of Education, University of Port Harcourt. The reliability index of 0.81 was established using Cronbach Alpha technique. For the purpose of data analysis, 45 and 1500 copies of questionnaire were retrieved from the principals and teachers respectively and were used for data analysis.Mean and standard deviation were the descriptive statistics employed to answer the research questions while z-test was used to test the null hypotheses at 0.05 level of significance. The study revealed inadequate provision, low extent of utilization and low level of maintenance of physical resources in the secondary schools in Rivers State.It was recommended based on the findings of the study among others that the government through a collaborative effort with the private sector should ensure that physical resources are provided in sufficient quantity in the school.